2019
DOI: 10.1029/2019gl083960
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of aerosol‐cloud interactions to mid‐Piacenzian seasonally sea ice‐free Arctic Ocean

Abstract: Forcings and feedbacks controlling the seasonally sea ice‐free Arctic Ocean during the mid‐Piacenzian Warm period (3.264–3.025 Ma, MPWP), a period when CO2 level, geography, and topography were similar to present day, remain unclear given that many complex Earth System Models with comparatively higher skills at simulating twentieth century Arctic sea ice tend to produce perennial Arctic sea ice for this period. We demonstrate that explicitly simulating aerosol‐cloud interactions and the exclusion of industrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 69 publications
0
24
1
Order By: Relevance
“…These new parameterizations in CAM5 produce a cloud simulation that agrees much better with satellite observations (Kay (Feng et al, 2019), the last glacial maximum (Zhu et al, 2017a), Heinrich events (Zhu et al, 2017b), and the last millennium (Otto-Bliesner et al, 2015;Thibodeau et al, 2018). To make the model suitable for a paleoclimate simulation with a high CO 2 level, the model code has been slightly modified to incorporate an upgrade to the radiation code that corrects the missing diffusivity angle specifications for certain longwave bands.…”
Section: Cesm Model Descriptionmentioning
confidence: 99%
“…These new parameterizations in CAM5 produce a cloud simulation that agrees much better with satellite observations (Kay (Feng et al, 2019), the last glacial maximum (Zhu et al, 2017a), Heinrich events (Zhu et al, 2017b), and the last millennium (Otto-Bliesner et al, 2015;Thibodeau et al, 2018). To make the model suitable for a paleoclimate simulation with a high CO 2 level, the model code has been slightly modified to incorporate an upgrade to the radiation code that corrects the missing diffusivity angle specifications for certain longwave bands.…”
Section: Cesm Model Descriptionmentioning
confidence: 99%
“…Lunt et al, 2012). Haywood et al (2013aHaywood et al ( , 2013b discussed the possible contributing factors to the noted discrepancies in DMC, noting three primary causal groupings: uncertainty in model boundary conditions, uncertainty in the interpretation of proxy data and uncertainty in model physics (for example, recent studies have demonstrated that this modelproxy mismatch has been reduced by including explicit aerosol-cloud interactions in the newer generations of models (Sagoo and Storelvmo 2017;Feng et al, 2019)).…”
Section: From Pliomip1 To Pliomip2mentioning
confidence: 99%
“…This data-model discord may have been caused by uncertainties in model physics, boundary conditions, or reconstructions (Haywood et al, 2013a) Uncertainties in model physics include unconstrained forcings and uncertainties in model parameters. It was found that the inclusion of chemistry-climate feedbacks from vegetation and wildfire changes leads to substantial global warming (Unger and Yue, 2014, while excluding industrial pollutants and explicitly simulating aerosol-cloud interactions (Feng et al, 2019), and decreasing atmospheric dust loading (Sagoo and Storelvmo, 2017) leads to increased Arctic warming in mPWP simulations. Similarly, in simulations of the Eocene, two models that implemented modified aerosols had better skill than other models at representing polar amplification (Lunt et al, 2020).…”
Section: In the Present Work We Analyze The Simulated Arctic Warmingmentioning
confidence: 99%
“…It is thus likely that other sources of error contribute to the data-model discord, such as uncertainties in model physics (e.g. Feng et al, 2019;Howell et al, 2016b;Lunt et al, 2020;Sagoo and Storelvmo, 2017;Unger and Yue, 2014) and boundary conditions (e.g. Brierley and Fedorov, 2016;Feng et al, 2017Feng et al, , 2017Hill, 2015;Howell et al, 2016b;Otto-Bliesner et al, 2017;Prescott et al, 2014;Robinson et al, 2011;Salzmann et al, 2013).…”
Section: Uncertaintiesmentioning
confidence: 99%